Total organic and inorganic carbon exchange through the Strait of Gibraltar in September 1997 - Dafner, Evgeny; Gonzalez-Davila, M; Santana-Casiano, JM; Sempéré, Richard (Deep Sea Research Part I: Oceanographic Research Papers, 2001)
The total organic carbon (TOC) and total inorganic carbon (CT) exchange between the Atlantic Ocean and the Mediterranean Sea was studied in the Strait of Gibraltar in September 1997. Samples were taken at eight stations from western and eastern entrances of the Strait and at the middle of the Strait (Tarifa Narrows). TOC was analyzed by a high-temperature catalytic oxidation method, and CT was calculated from alkalinity–pHT pairs and appropriate thermodynamic relationships. The results are used in a two-layer model of water mass exchange through the Strait, which includes the Atlantic inflow, the Mediterranean outflow and the interface layer in between. Our observations show a decrease of TOC and an increase of CT concentrations from the surface to the bottom: 71–132 μM C and 2068–2150 μmol kg−1 in the Surface Atlantic Water, 74–95 μM C and 2119–2148 μmol kg−1 in the North Atlantic Central Water, 63–116 μM C and 2123–2312 μmol kg−1 in the interface layer, and 61–78 μM C and 2307–2325 μmol kg−1 in the Mediterranean waters. However, within the Mediterranean outflow, we found that the concentrations of carbon were higher at the western side of the Strait (75–78 μM C, 2068–2318 μmol kg−1) than at the eastern side (61–69 μM C, 2082–2324 μmol kg−1). This difference is due to the mixing between the Atlantic inflow and the Mediterranean outflow on the west of the Strait, which results in a flux of organic carbon from the inflow to the outflow and an opposite flux of inorganic carbon. We estimate that the TOC input from the Atlantic Ocean to the Mediterranean Sea through the Strait of Gibraltar varies from (0.97±0.8)104 to (1.81±0.90)104 mol C s−1 (0.3×1012 to 0.56×1012 mol C yr−1), while outflow of inorganic carbon ranges from (12.5±0.4)104 to (15.6±0.4)104 mol C s−1 (3.99–4.90×1012 mol C yr−1). The high variability of carbon exchange within the Strait is due to the variability of vertical mixing between inflow and outflow along the Strait. The prevalence of organic carbon inflow and inorganic carbon outflow shows the ...